An Intraseasonal Variability in CO2 Over the Arctic Induced by the Madden‐Julian Oscillation. Issue 3 (6th February 2018) - Li, King‐Fai
Abstract: Variability of atmospheric CO2 must be well understood for us to better characterize the anthropogenic CO2 release from the surface. A previous study revealed the influence of the Madden‐Julian Oscillation (MJO) to tropical midtropospheric CO2 via convection. In this work, the observations by NASA's Atmospheric Infrared Sounder are used to further examine the MJO impact on the CO2 concentration over the Arctic. A composite analysis shows that the CO2 north of 60°N varies with a peak‐to‐peak amplitude of 1.2 ± 0.2 ppm over the MJO cycle. An empirical correlation analysis is applied to examine possible effects of retrieval bias and dynamics on the MJO‐related CO2 anomalies. It is shown that the spatial pattern of the MJO‐related Arctic CO2 anomalies closely resembles that of the isentropic potential vorticity anomalies at 475 K. Key Points: The CO2 north of 60°N varies with an amplitude of ±0.6 ppm over the MJO cycle The spatial pattern of the MJO‐related Arctic CO2 anomalies resembles that of the isentropic potential vorticity anomalies at 475 K The reported CO2 variability would help improve chemistry transport modeling